Journal Research IMPLEMENTASI KEBIJAKAN PEMBERDAYAAN MASYARAKAT MELALUI PEMBERIAN MODAL USAHA: PEMBERIAN MODAL USAHA - Ulmi Qalsum, Andi Tenri; Memang, Raja; Putera, Wahyudi; Wahyuti, Wahyuti; Iriani, Nisma; Saripuddin, Saripuddin (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
The purpose of this study was to determine the policy implementation of the business capital provision program through Village-Owned Enterprises (BUMDes) as an effort to empower the community's economy in Era Baru Village, Tellulimpoe District. This research uses qualitative research methods. The data sources used in this research are primary data and secondary data. The sampling method in this study uses a type of Non probability sampling with Purposive sampling technique. The data collection techniques used are data collection, data reduction, data presentation and conclusion drawing. The results showed that the business capital provision program in Era Baru Village has succeeded in empowering the community by increasing income through BUMDES which manages various types of businesses. The research generated new insights into the effectiveness of village business management, including financial transparency and business sustainability. In addition, the findings provide practical recommendations for the development of empowerment models that can be applied in other villages, as well as encouraging increased capacity of managers and community participation in program planning and implementation